Communication of information and knowledge about COVID-19: Analysis of websites of Spanish and Brazilian universities - Medina-González, Viena; Puerta-Díaz, Mirelys [UNESP]; Almansa-Martínez, Ana (Instituto Universitario de Lisboa (ISCTE-IUL), 2021)
The institutional communication plays a central role in health crisis situations, with websites being key tools for risk communication. The efficient use of these platforms allows universities to promote transparency and strengthen relationships of trust with their community in pandemic scenarios. A comparative analysis between websites of spanish and brazilian universities about the information and knowledge that communicate in relation to COVID-19 is performed. For this, the subject of knowledge communication, the identifying elements of this communication on the websites of universities and approaches in risky situations are addressed. The research is descriptive-analytical type with a mixed approach. It is a case study based on content analysis, in addition to bibliographic review and documentary analysis. The tool used was the Wayback Machine, which allowed analyzing the changes in communication approaches and behavior of publications on COVID-19 according to the history of the websites. The convergences between the communicative practices of the analyzed sites are featured, despite the difference of contexts, mainly from the dissemination of content on the initiatives and projects and the alternatives of interaction with the public. Through of these communication spaces, the universities have given an image of a key institution in social changes, as well as the support and benefits that it can bring from the fulfilling of their social responsibility through the university-society relationship.
Comunicación de información y conocimiento sobre COVID-19: Análisis de sitios web de universidades Españolas y Brasileñas
Keywords: COVID-19; Information; Knowledge communication; Risk communication; Universities; Websites